A Toolkit for Practice-Based Learning of Mechanisms in Industrial Design Education: An Application of a Method Combining Deductive and Inductive Learning - Yavuzcan, H. Güçlü; Gür, Barış (Design and Technology Education: An International Journal, 2020)
Industrial design education is focused on teaching a combination of various interdisciplinary competencies. One of these projected learning outcomes is to be able to design mechanisms in order to fulfil certain mechanical constraints in products. Studies show that theoretical knowledge supported by practice helps to teach industrial design students the mechanisms. In the current situation in Turkey, practice-based courses are designed with a similar purpose. However, graduates severely lack mechanical design skills. In this study, a two-staged toolkit of a holistic flow is introduced to prevent the deficiency mentioned above. In the toolkit, mechanisms are taught by combining deductive and inductive approaches, instead of a directly inductive conventional approach. The toolkit is applied to 36 sophomore year students. Assessments of the students and their self-evaluations are collected and analysed. Findings show that the toolkit can be beneficial for teaching of mechanisms to ID students through some revisions.